Atividades experimentais de física no ensino fundamental II: estudo com professores em formação inicial - Silva, Roberto Oliveira da (2019)
The present study intends to analyze, through contemporary references, how teachers in the process of initial formation appropriate models of experimental activities which differed from that experienced in their the undergraduate. In addition, it seeks to analyze if the discussions about this new model contribute to instituting a new vision about the role of these activities in learning in Physics, especially in elementary education. This study it is based on the understanding that there is a difficulty for teachers in the operationalization of constructivist proposals linked to activities in the didactic laboratory, and that the contents of Physics have been characterized as difficult to understand by elementary students II. In this context, it is sought to dialogue with new perspectives of experimental activities, fomenting this model in a training course of Physics teachers. The problem presented is evident when we identify that in these initial training courses, students are faced with traditional models of experimental activities, so, they need to transpose this model to the level of schooling in which they will act. This situation ends up being conflicting for academics who need to operationalize a different model of what they have experienced. In other words, they must reorganize the role of experimental activities in the construction of knowledge in the epistemological and pedagogical fields, for the laboratories in the undergraduate courses emphasize and prioritize the experimental method and the initiation of research, a distinct situation from the role that these activities must have when inserted in basic education. The above shows the need to provide new models, based on theoretical and methodological insights that make possible the use of these activities as a strategic resource for the construction of knowledge. Leading to the following question as the guiding principle of the study: How future Physics/ Sciences teachers will welcome and appropriate the discussions about the role of experimental activities in basic education, facing a different model from what they experienced in their formation? To answer these questions, we elaborated a didactic module related to the subject and applied with academics of a degree in Physics. The module involves the historical discussion about the different visions associated with these activities and points out alternatives to the contemporary pedagogical perspectives with emphasis on constructivism. In addition, the module includes the presentation of didactic equipment constructed with materials of easy acquisition, and discusses how they can be used in elementary education, which characterizes the educational product associated with the study. For the evaluation of the didactic module and as a way of answering the initial questioning, the study uses a qualitative and participant research, focusing on the analysis of an activity carried out at the beginning and at the end of the didactic module and in a semi-structured interview with a group of participants. The results of these two instruments show that graduates are aware that the didactic proposal to be used in basic education differs from that undergone in undergraduate courses, since the objectives associated to their use are distinguished in both epistemological and pedagogical terms. The educational product resulting from this study refers to videos involving the process of construction and use of didactic equipment that are freely available on the PPGECM website, such as the eduCapes Portal <http://educapes.capes.gov.br/handle/capes/431619>.